Formulation of poultry feed with supplementation protein content from Trichanthera Gigantea and Morus Alba leaves meal for Japanese quail (Coturnix Japonica) - Nur Atika Husna Kamal Mohamed (2022)
The poultry industry in Malaysia is a major source of meat protein. Feed, particularly the protein source ingredient, is the most critical single cost associated with poultry production. Because feed contribute for 60% to 70% of total production costs, any effort to reduce feed costs will result in a significant reduction in total feed production costs. This study aims to identify the best protein source ingredient and formulation for Japanese quail's diet using Design Expert Software Version 7.1 through Central Composite Design (CCD) as a statistical tool. This quail formulation diet included four main ingredients: Madre de agua leaves meal (MDALM), Mulberry leaves meal (MLM), rice bran (RB), and fish meal (FM) as a protein source. The recommended optimum value was 29.5 %, 27.5 %, and 19.5 % for leaves meal (MDALM & MLM), RB, and FM, respectively, resulting in an optimum protein content of 27.0116 % for MLM inclusion. In the future, the formulation of quail feed from leaves meal can be an option in the poultry industry. Together with cost-effectiveness, leaves meals have a high potential to replace pricey and imported ingredients in the feed industry.